Plasma Arginine Levels and Blood Glucose Control in Very Preterm Infants Receiving 2 Different Parenteral Nutrition Regimens. (February 2014) - Burgess, Laura; Morgan, Colin; Mayes, Kelly; Tan, Maw
Background : Improving parenteral nutrition (PN) amino acid (AA) intake in very preterm infants is associated with less hyperglycemia. AAs stimulate newborn insulin secretion with arginine, demonstrating a specific effect. We hypothesized that low arginine levels would be associated with increased insulin-treated hyperglycemia and higher mean daily blood glucose levels in very preterm infants. Methods : We performed a secondary analysis on previous study data comparing high-protein/calorie PN (HPC-PN) and control groups in infants <29 weeks' gestation. Infants were substratified (within original groups) according to high (highARG) and low (lowARG) plasma arginine levels on days 8–10 using a reference population-derived threshold for high/low arginine (57 µmol/L). Daily protein, arginine, carbohydrate intake, mean daily blood glucose, and insulin treatment data from the first 15 days of life were collected. Results : Control group infants (n = 60) were stratified into lowARG (n = 41) and highARG (n = 19) groups. There were no differences in basic demographic data or carbohydrate intake. LowARG infants had higher mean daily blood glucose levels ( P < .05) and a trend to more insulin treatment on days 6–10. HPC-PN group infants (n = 55) were stratified into lowARG (n = 33) and highARG (n = 22) groups. LowARG infants had lower gestation and birth weight and were sicker than highARG infants. There were no differences in carbohydrate intake. LowARG infants had higher mean daily blood glucose levels ( P < .01) and more insulin treatment ( P < .01) on days 1–5 and 6–10. Insulin-treated hyperglycemia was also associated with low plasma glutamine levels. Conclusion : Low plasma arginine levels (≤57 µmol/L) in very preterm infants are associated with poorer blood glucose control.